Activation of peracetic acid by metal-organic frameworks (ZIF-67) for efficient degradation of sulfachloropyridazine - Duan, Jun; Long Chen; Ji, Haodong; Li, Peishen; Li, Fan; Liu, Wen (Chinese Chemical Letters, 2022)
Peracetic acid (PAA)-based system is becoming an emerging advanced oxidation process (AOP) for effective removal of organic contaminants from water. Various approaches have been tested to activate PAA, while no previous researches reported the application of metal-organic frameworks (MOFs) materials for PAA activation. In this study, zeolitic imidazole framework (ZIF)-67, a representative MOFs, was facile synthesized via direct-mixing method at room temperature, and tested for PAA activation and sulfachloropyridazine (SCP) degradation. The as-synthesized ZIF-67 exhibited excellent performance for PAA activation and SCP degradation with 100% of SCP degraded within 3 min, owing to the specific MOFs structure and abundant Co2+ sites. The pseudo-first-order kinetic model was applied to fit the kinetic data, with rate constant k1 of ZIF-67 activated PAA system 34.2 and 156.5 times higher than those of conventional Co3O4 activated PAA and direct oxidation by PAA. Radical quenching experiments and electron paramagnetic resonance (EPR) analysis indicated that CH3C(O)OO• played a major role in this PAA activation system. Then, the Fukui index based on density functional theory (DFT) calculation was used to predict the possible reaction sites of SCP for electrophilic attack by CH3C(O)OO•. In addition, the degradation pathway of SCP was proposed based on Fukui index values and intermediates detection, which mainly included the S-N bond cleavage and SO2 extrusion and followed by further oxidation, dechlorination, and hydroxylation. Therefore, ZIF-67 activated PAA is a novel strategy and holds strong potential for the removal of emerging organic contaminants (EOCs) from water.
Keywords: Acetylperoxy radical; DFT calculation; Emerging organic contaminants; Metal-organic frameworks; Peracetic acid activation; Zeolitic imidazole framework (ZIF)-67